Economic GIG In Indonesia: Challenges And Opportunities For Gen Z And Milenials - Joko Nugroho; Verus Hardian; Dingot Hamonangan Ismail; Joko S Dwi Raharjo (International Publisher, 2023)
This research discusses how the Development and Implementation of the Gig Economy in Indonesia and how Gen Z and Gen Millennials deal with it. Research using the literature review method shows that Gig Economy has developed in Indonesia, but in its implementation it is still stuck in the transportation and business sectors between goods, food and people. The development of the Gig Economy in Indonesia has not yet explored the creative economy industrial sector and other knowledge-intensive sectors.